Ostergren, Robert C. i Le Bossé, Mathias (2011): The Europeans: A Geography of People, Culture and Environment. Second Edition - Wilbrand, Stephanie (Documents d'Anàlisi Geogràfica, 2012)
Ostergren, Robert C. i Le Bossé, Mathias (2011) The Europeans: A Geography of People, Culture and Environment. Second Edition Nova York (EUA): The Gilford Press, X + 432 p. ISBN: 978-1-59385-384-6 (pbk.) – 978-1-60918-140-6 (hbk.)